Nitrofurantoin and Fosfomycin for the CRE and MDR uropathogens: are the choices still same? - Perween, Nusrat; Sultan, Asfia; Akhtar, Anees; Khan, Fatima; Rizvi, Meher; Khan, Haris M.; Ahmad, Manzoor (International Journal Of Community Medicine And Public Health, 2020)
Background: Urinary tract infection (UTI) is one of the most common bacterial infections, affecting 150 million people each year worldwide with substantial clinical and financial burden. With upcoming multi drug resistance (MDR) and carbepenem resistance among uropathogens there is urgent need to explore other new or old treatment options like nitrofurantoin and fosfomycin trometamol. Methods: This is a cross-sectional (descriptive study) conducted over 6 month’s period from October 2019 to March 2020. Out of 9045 urine samples, 1788 (19.8%) were positive (1721 samples with single organism and 67 samples with 2 organisms). Total 1855 isolates were identified and antimicrobial susceptibility was performed by Kirby-Bauer method and VITEK 2 system. Methicillin‑resistant Staphylococcus aureus (MRSA), vancomycin resistant enterococci (VRE), multi drug resistance (MDR) and metallo‑beta‑lactamases (MBL) production was detected. Results: E. coli 41.8% was found commonest followed by enterococcus species (21.6%). Methicillin resistance was 66% while 1.8% were VRE. 429 (34.5%) were CRE (carbapenem resistant enterobacteriales) out of which, 154 (36%) were MBL while 188 (44%) were detected as serine carbapenemase producers via modified carbapenem inactivation method (mCIM) and EDTA-modified carbapenem inactivation method (eCIM) testing. Among 742 (40%) MDR, fosfomycin was effective in 611 (82.3%) while 331 (77.1%) of the CRE isolates were susceptible to fosfomycin. Conclusions: Fosfomycin should be reserved for MDR and nitrofurantoin should be used cautiously otherwise resistance will increase to these drugs in the coming days.